A Review Study of Physical Education Pedagogy in Turkey - Fatih Dervent; Erhan Devrilmez; Mehmet Dalkılıç; Ekrem Yasin Tabak (Selcuk University, 2023)
Pedagogy is defined as a concept based on the transfer of teacher' knowledge and skills to the learner. Similar definition of pedagogy has been detected on physical education field. Physical education pedagogy is examined in three sub-dimensions which are teaching physical education, physical education teacher education and curriculum. In this study, articles about physical education pedagogy published in scientific journals scanned in TR Index were examined using document review and descriptive content analysis methods. Totally 2157 studies from six journals publishing in TR Index were accessed and 18 articles were selected. The first and second authors of the study examined and analyzed the studies. Inter-researcher consistency was 93.4 % which indicated high consistency. Results showed that five studies for teaching physical education, six studies for physical education teacher education and seven studies for curriculum sub-domains of pedagogy were published in TR Index. Teaching physical education studies focused on effectiveness of models, materials and instructional design. In physical education teacher education sub-domain, studies examined effectiveness of peer teaching model, teaching practice and scale development. Results also indicated that all seven curriculum studies focused on examination of renewed or updated physical education and sport curriculum. As a conclusion, the number of articles on physical education pedagogy published in the TR Index was not sufficient considering the total number of published studies. Curriculum studies were generally carried out shortly after the curriculum updates in Turkey. There is a need for longitudinal studies that examine the long-term effects of curricula and evaluate the curricula in terms of all stakeholders affected by the program.